1990
DOI: 10.1039/ft9908600145
|View full text |Cite
|
Sign up to set email alerts
|

Density measurement by oscillating tube. Effects of viscosity, temperature, calibration and signal processing

Abstract: A frequency counter and precision thermostat, designed to operate in conjunction with an Anton Paar DMA 602 oscillating tube densitometer, have been built. The apparatus is capable of rapid density determinations. It can detect density changes of less than 5 x g ~m -~and allows densities of low viscosity materials to be determined to an accuracy of f 5 x g ~m -~if a suitable calibration standard is available. The effect of t h e viscosity of the samples on the density readings has been found to be significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 6 publications
1
61
0
1
Order By: Relevance
“…Several studies of this effect [11][12][13][14][15][16][17][18][19] have shown that the shape of the deviation is similar for all the studied vibrating-tube densimeters from Anton Paar. However, the reasons for this do not seem to be well understood.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies of this effect [11][12][13][14][15][16][17][18][19] have shown that the shape of the deviation is similar for all the studied vibrating-tube densimeters from Anton Paar. However, the reasons for this do not seem to be well understood.…”
Section: Introductionmentioning
confidence: 95%
“…The effect of viscosity on the density measurements made by U-tube densimeters has been extensively studied experimentally [11][12][13][14][15][16][17][18][19] and, recently, the increasing interest in high viscosity liquids has intensified the awareness in this effect [15][16][17][18]. However, to the knowledge of the authors, no theoretical study has been published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest attempts at determining this quantity in RTILs resulted in large differences between the results obtained by some authors, which has been ascribed to an unusually strong influence of impurities on density [14]. Also the most commonly used technique for determining density, which uses a vibratingtube densimeter, is allegedly subject to systematic errors due to the ''damping effect" arising from the typically high viscosity of RTILs [15]. By now, impurities in RTILs have been substantially reduced, their influence on density at least partly elucidated and the consequences of the damping effect avoided by using a variety of techniques most of which require the knowledge of the sample viscosity [16][17][18].…”
Section: Introductionmentioning
confidence: 96%
“…[5,7] The density of 1 was measured in the temperature range of 15-50 8C in steps of 5 K using a vibrating-tube densiom- eter. [16] The linear temperature dependence is given by Equation (1):…”
mentioning
confidence: 99%